KREASI BONEKA DARI POT BUNGA UNTUK ANAK BERKESULITAN BELAJAR SEKOLAH TALENTA JAKARTA - Julius Andi Nugroho; Rini Cristanti; Irine Can; Cavin Joo Dauneeaaron (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
The Special Child Care Foundation (YPAS) established a Talenta School for children with learning difficulties, who have difficulties in learning activities such as reading (dyslexia), writing (dysgraphia), counting (dyscalculia), attention deficit disorder (ADD) / attention deficit hyperactivity disorder (ADHD). Art is a routine necessity that is indispensable, because it can activate the right side of human brain. There are many kinds of art, one of which is making dolls made of plastic flower pots with illustration techniques. During the pandemic, learning activities in art and hand craft are reduced, caused by online learning. The doll pots are made of plastic to keep participants safe, but are made roughly like pottery. The making process is not difficult because participants can pour ideas in the form of pictures to be painted onto the surface of the pot. The purpose of the workshop is to make doll pots that can eliminate boredom at home and also increase child’s creativity and imagination, because the drawing is customized according to the child's wishes. The design method used qualitative techniques by interviewing the head of the Talenta School to find out partner problems. This workshop trains children with learning difficulties’ motor skills and adds new insights, increases creativity and provokes ideas through the child's imagination. The discussion that has been carried out is correcting during training and what needs to be improved for future training, because the workshop for children with learning difficulties is different from common children. The results that have been made are in the form of modules, video tutorials, activity videos, power point of teaching materials, certificates, research week and proceedings.